Distal connectivity causes summation and division across mouse visual cortex - Sato, Tatsuo K (Nat Neurosci, 2013)
Neurons in different locations across the cortex are connected through polysynaptic networks involving both excitation and inhibition. To probe the functional impact of such networks we used optogenetic stimulation to trigger antidromic spikes in a local region of primary visual cortex. This local activity caused two effects at distal locations: summation and division. The balance between the two depended on visual contrast, and a normalization model precisely captured these effects.